The transformative role of the media in the formation of virtuous citizens: A contribution to reconciliation in a post-apartheid South Africa - E. Baron (Acta Theologica)
The significant role that the media played during the apartheid years in South Africa is staggering. Abundant evidence suggests that, during those years, the print media served as instruments for propaganda, for the apartheid regime, while the Argus group, for instance, exposed the atrocities and human rights violations of the same regime. However, 24 years into democracy, what is the role of the media in a post-apartheid South Africa, where citizens still suffer from the ghosts of apartheid, the continued human rights violations, racial discrimination, and related issues that make it seem as if South Africa is “irreconcilable”? This question will be addressed by drawing from a recent study conducted by the author that has demonstrated the role of newspapers in moral formation as a positive perspective on the media in the process of reconciliation. The author argues that the print media play their role through their articulation of a good society, through regular reporting on issues related to reconciliation, which can be regarded as an exercise in vigilance to help their readers identify, and address immoral behaviour that may impede achieving reconciliation. Through such reporting, the audience could become virtuous people that will serve as assets in the process and journey for reconciliation in South Africa.